Ultra-small dispersed CuxO nanoparticles on graphene fibers for miniaturized electrochemical sensor applications. Issue 48 (9th September 2019) - Zeng, Jinfeng; Ding, Xiaoteng; Chen, Liwei; Jiao, Le; Wang, Yuze; Windle, Christopher D.; Han, Qing; Qu, Liangti
Abstract : A graphene microfiber modified with ultrafine Cu x O nanoparticles (Cu x ONPs/GF) is fabricated by direct annealing of electrodeposited nano-sized copper-based metal–organic frameworks (HKUST-1) and used as an electrode for nonenzymatic H2 O2 sensing. Abstract : A graphene microfiber (GF) modified with ultrafine Cu x O nanoparticles (Cu x ONPs/GF) has been fabricated by direct annealing of electrodeposited nano-sized copper-based metal organic frameworks (HKUST-1) and used as an electrode for nonenzymatic H2 O2 sensing. Benefiting from the unique microfiber architecture and synergetic effects, as well as strong coupling between components with many active sites and boosted electron transport, the Cu x ONPs/GF electrode shows prominent sensitivity, selectivity and long-term operational stability for the detection of H2 O2 . Further work successfully applied this Cu x ONPs/GF electrode to detection of H2 O2 in real samples such as milk and human serum. These results indicate that the Cu x ONPs/GF is a promising mini-sized sensor in electrochemical analysis.